Double-, energy-, angle- differential and total yield cross section data of 58Ni(n,a)55Fe reaction - Tsabaris, C.; Vlastou, R.; Papadopoulos, C. T.; Kalfas, C. A.; Wattecamps, E.; Rollin, G. (HNPS Advances in Nuclear Physics, 2020)
The double-, energy-, angle- differential cross section data, and the total yield of 58Ni(n,α)55Fe reaction is investigated in the neutron energy range between 2 and 9 MeV. The measurements were performed with the prompt detection method, detecting the alpha particles of the reaction with a multitelescope consisted of five ΔΕ-ΔΕ-Ε telescopes, placed at angles 14, 51, 79, 109 and 141 degrees relative to the neutron beam direction. The normalisation to the absolute units was made using the known total yield of the reference reactions 27Al(n,α)24Na and 58N(n,p)58Co. The cross section measurements were compared with previous measurements and with theoretical calculations performed with the STAPRE-H [1-4] code.